Adult life situations of Filipino women who experienced teenage childrearing a pseudo - cohort analysis - Castillo, Plenee Grace J. (Population Institute, College of Social Sciences and Philosophy, University of the Philippines Diliman, 2015)
The government and concerned sectors were particularly alarmed with the latest statistics on teenage childbearing in the country indicating a surge of more than 100 percent, from 6.3 percent in 2002 to 13.6 percent in 2013 (DRDF & UPPI, 2014). Teen pregnancy and early childbearing are generally regarded as being associated with various adverse social and economic life situations among young women that persist even until their adult life. However, local studies that document such association are lacking despite the increasing trend in teenage pregnancy in the country. Hence, this study aims to examine the adult the life situations, specifically, the highest educational attainment and socio-economic status of women who experienced teen childbearing vis-à-vis women who started childbearing in older years using a pseudo-cohort analysis approach. The study used a pooled sample of women 25-49 years old from the five most recent rounds (1993 to 2013) of the Philippine National Demographic and Health Survey (NDHS). The analytic sample consists of 33,427 women representing six five-year birth cohorts spanning a period of 30 years (1951-1980). Period effects given as “birth cohorts” were assessed with regards to their association with teen childbearing experience. Binary logistic regression models were used to uncover statistically significant associations of teen childbearing with two adult life adverse situations: failure to go beyond high school and poor socioeconomic status. Trends in educational attainment and socioeconomic status across birth cohorts were examined using the Mantel-Haenszel linear-by-linear association test and linear regression analysis. Study results show that 29 percent of Filipino women have experienced teen childbearing and this is true for birth cohorts covering the period 1951-1975. In addition, regardless of region of residence, type of place of residence, and birth cohort, women who experienced teen childbearing were less likely to have gone beyond high school but not necessarily more likely to be poor compared to their older counterparts. Overall, the odds of having gone beyond high school increased across successive cohorts while the odds of being poor in adult life also increased across cohorts for both teen and older mothers. Cohort-to-cohort variations were observed that suggest the possible influence of societal events in the adult situations of teen and older mothers.